To treat or not to treat – Successful hepatitis C virus eradication in a patient with advanced hepatocellular carcinoma and complete response to sorafenib - Waidmann, Oliver; Peveling-Oberhag, Jan; Eichler, Katrin; Schulze, Falko; Vermehren, Johannes (Zeitschrift für Gastroenterologie, 2017)
Background and aims Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death worldwide. Infection with the hepatitis C virus (HCV) is one of the most frequent underlying diseases leading to HCC development. Sorafenib is the standard of care for HCC patients not amenable to local treatment, resection, or liver transplantation. Although overall survival can be increased, objective response rates in patients treated with sorafenib are low. In HCC patients who underwent resection or ablation, HCV eradication with interferon-based regimens reduces the risk of recurrence. However, it is not known and under strong debate if patients with HCC should be treated with interferon-free regimens. Furthermore, it is not known if patients with advanced HCC at the time of diagnosis should be treated with antiviral therapy.Methods A patient with histologically confirmed advanced-stage HCC due to HCV-related cirrhosis was treated with sorafenib according to current guideline recommendations. Furthermore, he received subsequent treatment with direct antiviral agents (DAAs).Results The patient achieved a complete response after sorafenib treatment was initiated. Sorafenib treatment was terminated 1 year after complete response. As no recurrence of HCC was evident after treatment cessation, antiviral treatment was initiated with paritaprevir/ritonavir, ombitasvir, dasabuvir, and dose-reduced ribavirin because of chronic kidney disease. The patient achieved a sustained viral response.Conclusions Complete response to sorafenib treatment is scarce. Antiviral treatment should be considered in such patients as well as in patients with HCC who underwent resection or ablation.
Keywords: Hepatozelluläres Karzinom; Hepatitis C; Sorafenib; Antivirale Therapie; Direct Antiviral Agent; Interferon-freie Therapie